Income Smoothing e gerenciamento de resultados por diferimento tributário sobre o resultado em companhias listadas na B3 - Ferreira, Júlio César (Universidade do Vale do Rio dos Sinos, 2021)
This research deals with deferred income taxes arising from temporary differences and their effects on the companies' results, in the context of the adoption of the International Financial Reporting Standards (IFRS) and regulated by NBC TG 32 -Taxes on Profits. The objective is to analyze the impact of tax deferrals as an income smoothing and results management practice in companies listed on B3. We used public data extracted from the Economática® database and the Brasil, Bolsa e Balcão (B3) website. The analysis period comprised 2010 to 2020. This period is justified by covering the changes related to convergence to IFRS international accounting standards, through NBC TG 32. As a metric for result management the Modified Jones model was used and as a procedure to identify the presence of smoothed results, the measure called (EM1) of Leuz, Nanda and Wisocky (2003) was adopted as a metric. To carry out this study, methodologically, the final sample was composed of 177 companies, resulting in 1947 observations. The data analysis occurred, initially, with the use of univariate statistics, to perform the descriptive analysis of the data. Later, to evaluate the impact of tax deferral on earnings management, the regression technique with panel data was used. To choose the panel model to be adopted, among fixed, random, or pooled effects, the Breusch-Pagan, Chow, and Hausman tests were performed, resulting in the pool model being the most appropriate. The analysis of the descriptive statistics of the values of the deferred taxes on profit revealed that the deferred taxes positively affect the companies' results, increasing the profit or decreasing the loss for the period. In the model estimations, the degrees of management and smoothing of results showed a significant negative interaction with deferred taxes, indicating that companies that practice management and smoothing of results have a lower incidence of deferred taxes, i.e. there is a tendency for companies with more management and smoothing of results to recognize less deferred taxes. Thus, a more pronounced association between Deferred Taxes and Earnings Management was not identified. Furthermore, the influence of deferred taxes on earnings management and smoothing was identified, to the extent that the higher the presence of deferred taxes, the lower the level of earnings management and smoothing present in the companies' statements. As a result of the results, it was found that the Agency Theory provides support to the phenomenon studied, given that good accounting practices through the NBC TG-32 reflect on the quality of accounting information, being capable of promoting the reduction of informational asymmetry problems between economic agents, to the extent that alignment and monitoring of contractual agency relations are established. And, finally, the contribution of this thesis is in presenting a trend of institutional change in manager's behavior in the face of opportunistic motivation, contributing to the credibility of data in accounting and fiscal reports and also to the efficiency of this information as relevant for the Brazilian capital market.
Keywords: Income Smoothing; Gerenciamento de resultados; Tributos diferidos sobre lucros; Earnings management; Deferred income taxes; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis